Three research priorities for just and sustainable urban systems: Now is the time to refocus - Joe F. Bozeman; Shauhrat S. Chopra; Philip James; Sajjad Muhammad; Hua Cai; Kangkang Tong; Maya Carrasquillo; Harold Rickenbacker; Destenie Nock; Weslynne Ashton; Oliver Heidrich; Sybil Derrible; et al. (Journal of Industrial Ecology, 2023)
Now is the time to refocus efforts in urban research and design. A changing climate and extreme weather events are presenting unique challenges to urban systems around the world. These challenges illuminate the social barriers that accompany disruptive events such as resource inequities and injustices. In this perspective, we provide three research priorities for just and sustainable urban systems that help to address these matters. The three research priorities are: (1) social equity and justice, (2) circularity, and (3) digital twins. Conceptual context and future research directions are provided for each. For social equity and justice, the future directions are mandatory equity analysis and inclusionary practices, understanding and reconciling historical injustices, and intentional integration with diverse community stakeholders. For circularity applications, they are better metrics for integration, more robust evaluation frameworks, and dynamic modeling at multiple spatial and temporal scales. Future directions for digital twins include developing principles to reduce complexity, integrating model and system components, and reducing barriers to data access. These research priorities are core to meeting several of the United Nations Sustainable Development Goals (i.e., 1—No Poverty, 8—Decent Work and Economic Growth, 10—Reduced Inequalities, and 11—Sustainable Cities and Communities). Useful social and technical matters are discussed throughout, where we highlight the importance of prioritizing localized research efforts, provide guidance for community‐engaged research and co‐development practices, and explain how these priorities interact to align with the evolving field of industrial ecology.